130k views
0 votes
50 POINTS! Arrange the steps to solve this problem. 9 steps. 50 POINTS!

50 POINTS! Arrange the steps to solve this problem. 9 steps. 50 POINTS!-example-1
50 POINTS! Arrange the steps to solve this problem. 9 steps. 50 POINTS!-example-1
50 POINTS! Arrange the steps to solve this problem. 9 steps. 50 POINTS!-example-2
50 POINTS! Arrange the steps to solve this problem. 9 steps. 50 POINTS!-example-3
50 POINTS! Arrange the steps to solve this problem. 9 steps. 50 POINTS!-example-4
User Brazeredge
by
5.7k points

2 Answers

7 votes

Answer:

...

Explanation:

User GloryFish
by
6.7k points
2 votes


\left\{\begin{array}{ccc}x+y=-2\\2x-3y=-9\end{array}\right\\\\\text{multiply the first equation by 3}\\3(x+y)=3(-2)\qquad|\text{use distributive property}\\3x+3y=-6\\\\\underline{+\left\{\begin{array}{ccc}3x+3y=-6\\2x-3y=-9\end{array}\right}\qquad\text{add 3x+3y=-6 to 2x-3y=-9, and solve for x}\\.\qquad5x=-15\qquad|:5\\.\qquad x=-3\\\\\text{Substitute the value of x in the first equation (x+y=-2)}\\\\-3+y=-2\qquad|+3\\y=1\\\\\text{The solution for the system of equations is (-3, 1)}

User Kvista
by
6.5k points